Assessment of Different Cetirizine Dosing Strategies on Seasonal Allergic Rhinitis Symptoms: Findings of Two Randomized Trials - Eduardo R. Urdaneta MD; Mitesh K. Patel PharmD; Kathleen B. Franklin BSN, RN; Xiaoyan Tian MSc; Mei-Miau Wu DrPH (Allergy & Rhinology, 2018)
Background Cetirizine has been shown to be effective for relief of seasonal allergic rhinitis (SAR) symptoms. Allergic rhinitis symptoms have been reported to have circadian variations, with symptoms tending to be most bothersome overnight and in the morning. Objective To evaluate the effects of different cetirizine dosing schedules in comparison to twice daily (BID) chlorpheniramine and placebo on SAR symptoms at 12 and 24 hours postdose. Methods Study 1 subjects received cetirizine 10-mg once daily in the morning (QAM), cetirizine 10-mg once daily at bedtime (QHS), cetirizine 5-mg twice daily, or placebo. Study 2 subjects received cetirizine 5-mg QAM, cetirizine 10-mg QHS, chlorpheniramine 8-mg BID, or placebo. The primary end point was total symptom severity complex (TSSC); TSSC was the sum of symptom severity ratings averaged over the 2-week study period. Post hoc analyses of reflective symptom severity assessed in the morning (TSSC AM ) and in the evening (TSSC PM ) were conducted to evaluate cetirizine’s effects at 12 and 24 hours postdose. Results In study 1, subject- and investigator-assessed TSSC was significantly lower in all cetirizine groups versus placebo ( P ≤ .003). In study 2, subject-assessed TSSC was significantly lower in all cetirizine groups versus placebo ( P ≤ .04) and was numerically lower for investigator-assessed TSSC. Post hoc analyses demonstrated that cetirizine significantly improved TSSC AM at 12 and 24 hours postdose versus placebo in both studies regardless of dosing schedule. TSSC PM significantly improved at 12 and 24 hours postdose in all study 1 cetirizine groups versus placebo. In study 2, versus placebo, TSSC PM significantly improved at 12 hours postdose in cetirizine 5-mg QAM group and numerically improved at 24 hours postdose in cetirizine 10-mg QHS group. Conclusion Regardless of dosing regimen, cetirizine demonstrates effective 24-hour relief of SAR symptoms, particularly on TSSC AM , which assesses overnight and early morning symptom control.